Characterization and application of assistance systems in digital engineering. Issue 1 (2021) - Stark, Rainer; Brandenburg, Elisabeth; Lindow, Kai
Abstract: A broad range of assistance systems can be found in manufacturing practice as well as in the corresponding literature. Similarly, it can be observed that there is a growing need for and an increasing supply of assistance systems of all kinds. However, for digital manufacturing, the assistance systems are not clearly characterized. The diversity in application areas and possible uses varies and there are no possibilities for comparison. This paper addresses the topic of assistance systems and examines the various basic elements of engineering activities in terms of possible types of assistance systems based on research in manufacturing industry. Crucial aspects of assistance capabilities for engineering are elaborated and possible digital approaches are validated based on investigations in the field of aircraft engine design and assembly.